Farmers’ social networks and the diffusion of modern crop varieties in India - Negi, Digvijay Singh; Birthal, Pratap S.; Kumar, Anjani; Tripathi, Gaurav (Emerald Publishing Limited, 2022)
The main aim of this paper is to assess the relevance of caste-based social networks in the dissemination of technologies and innovations in the Indian agriculture.Using the unit-level data from a large-scale farm survey, this paper constructs a multidimensional index of social networks encompassing households' castes and information sources within the administrative boundaries of a district and subsequently assesses its association with the adoption of modern seeds of staple food crops.There is a strong effect of caste-based networks on the adoption of modern seeds of different crops, but the effect is linked to the stage of technological change, i.e. the network effect is stronger for the crop that has experienced late technological change. Further, the behavior of network members is found to have a bigger impact on the individuals' technology adoption decisions as compared to the characteristics of individuals in the network.Given likely, increases in demand for diverse information and limited outreach of public extension systems, the findings suggest that in a socially heterogeneous society the caste-based social networks can serve as an important channel for the dissemination of information and innovations.What is unique in this paper is that it constructs a multidimensional index of social networks embedding the farm households' castes and information sources within the administratively defined boundaries of a geographical region.